Research Transparency and Data Privacy – a fine balance - Tilbrook, Amy (International Journal of Population Data Science, 2018)
Preserving the confidentiality of information is of paramount importance to data controllers sharing data for research use. Work within the Administrative Data Research Network is built upon strict information governance and assurance protocols to minimise any privacy risks and maximise public benefit. However, research funders and publishers are ever more requiring research to be as transparent and open as possible, with increasing pressure to publish datasets underpinning the research. This is seen as crucial for both verification and to maintain the integrity of the research. While Safe Havens and data repositories provide some reassurance in terms of storage and citation, how can researchers prepare to walk this fine line between publisher and funder requirements and the need to protect privacy? This presentation will explore the issue of privacy vs research transparency from the viewpoints of researchers, safe haven providers and research co-ordinators. Examining such issues as disclosure control, statistical packages updating, public opinion and the potential impact of the new European data protection legislation, it will outline challenges and provide potential guidelines for researchers and administrators involved in administrative data research.